A genome‐scale TF–DNA interaction network of transcriptional regulation of Arabidopsis primary and specialized metabolism - Michelle Tang; Baohua Li; Xue Zhou; Tayah Bolt; Jia Jie Li; Neiman Cruz; Allison Gaudinier; Richard Ngo; Caitlin Clark‐Wiest; Daniel J Kliebenstein; Siobhan M Brady (Molecular Systems Biology)
Abstract Plant metabolism is more complex relative to individual microbes. In single‐celled microbes, transcriptional regulation by single transcription factors (TFs) is sufficient to shift primary metabolism. Corresponding genome‐level transcriptional regulatory maps of metabolism reveal the underlying design principles responsible for these shifts as a model in which master regulators largely coordinate specific metabolic pathways. Plant primary and specialized metabolism occur within innumerable cell types, and their reactions shift depending on internal and external cues. Given the importance of plants and their metabolites in providing humanity with food, fiber, and medicine, we set out to develop a genome‐scale transcriptional regulatory map of Arabidopsis metabolic genes. A comprehensive set of protein–DNA interactions between Arabidopsis thaliana TFs and gene promoters in primary and specialized metabolic pathways were mapped. To demonstrate the utility of this resource, we identified and functionally validated regulators of the tricarboxylic acid (TCA) cycle. The resulting network suggests that plant metabolic design principles are distinct from those of microbes. Instead, metabolism appears to be transcriptionally coordinated via developmental‐ and stress‐conditional processes that can coordinate across primary and specialized metabolism. These data represent the most comprehensive resource of interactions between TFs and metabolic genes in plants.